Guilt aversion and redistributive politics: A moral intuitionist approach - Gilles Le Garrec (Kiel Institute for the World Economy (IfW), 2013)
In mainstream economics individuals are supposed to be driven only by their self-interest. By contrast, surveys clearly show that people do care about fairness in their demand for redistribution. In this article, in the spirit of the new synthesis in moral psychology (Haidt, 2007: The new synthesis in moral psychology) the author proposes to modelize the voting behavior over redistribution as the interaction between (a) an automatic cognitive process which quickly generates intuitions on the fair level of redistribution, (b) a rational self-oriented reasoning which controls the feeling of guilt associated with fair intuitions. In addition, considering that guilt aversion depends on the cultural context, the author shows that the model exhibits a multiplicity of history-dependent steady states which may account for the huge difference of redistribution observed between Europe and the United States.
Keywords: D03; D64; D72; H53; 330; redistribution; voting behavior; fairness; behavioral economics